The Influence of Nutrition Knowledge and Food Choosing Attitude on Adolescent Eating Behavior in Kediri District - Stifani Dianisa Prafita Hadi; Rahayu Dewi Soeyono; Any Sutiadiningsih; Mauren Gita Miranti (Universitas Pendidikan Indonesia (UPI), 2023)
Adolescence is a period of transition from children to adults, during this period the food consumed must be considered both in terms of safety and nutrition. Balanced nutrition will determine their health in the future and prevent them from double nutritional problems. This study aims to identify the effect of nutritional knowledge and attitudes toward food choices on adolescent eating behavior. Sampling used purposive sampling with a total sample of 77 people aged 12-21 years. The research design used was observational with a cross sectional approach. The research was conducted in Kediri Regency, East Java through a survey method by distributing questionnaires online via the Google Form. Research data were analyzed using percentages in tabular form and data correlated between variables. The results of the analysis of data by sex showed that 67.53% of adolescents were female and 32.47% were male. The results of the subsequent analysis showed that 50.65% of adolescents had good nutritional knowledge, 64.94% of adolescents had sufficient attitudes to choose food and 61.04% of adolescents had sufficient eating behavior. The results of the correlation test between nutritional knowledge and the attitude of choosing food obtained a significant value of 0.160 which means that there is no significant relationship between the two variables. While the results of the correlation test between nutritional knowledge and eating behavior of adolescents and the attitude of choosing food with eating behavior both obtained a significant value of less than 0.005 which means that there is a significant relationship between the two variables. A multiple correlation value (R) of 0.005 was obtained, meaning that there was an influence between nutritional knowledge and attitudes towards choosing food on eating behavior in adolescents